Analysis of applying fin for charging process of phase change material inside H-shaped thermal storage. (December 2022) - Izadi, Mohsen; Hajjar, Ahmad; Alshehri, Hashim M.; Saleem, Arslan; Galal, Ahmed M.
Abstract: An H-shaped Double thermal storage unit has been studied numerically. A middle wall is sandwiched between two twin thermal storage cavities which are charging. The fins are attached to the middle wall to enhance the charging process. The set of equations modeling the charging process were solved using the Finite Element Method. The effects of different main parameters, namely thermal Fourier number, fin angle (symmetric cases) (−60 ≤ λ ≤ 60), 15 cases related to non-symmetric fin angle (−60 ≤ λ l ≤ 60) and ( − 60 ≤ λ r ≤ 60), and aspect ratio of fins (AR = 0.5–32) on the melting process of phase change material have been numerically studied. The results indicate that using fins for the cavity enhances the melting rate in the neighboring region due to the conductive heat transfer through the fins. Also, faster phase change material melting can be achieved by directing the fins upwards. Highlights: Passive variables on charging process inside a thermal storage were considered. Attached fins to the cavity enhances melting process of PCM. Directing the fins upwards results in faster PCM melting. Reducing the aspect ratio of the fins enhances PCM melting.